Spatial diversity and habitat characteristics of seagrass meadows with management recommendations in the Andaman and Nicobar Islands, India - Gole, Swapnali; Prajapati, Sumit; Prabakaran, Nehru; Das, Himansu; Kuppusamy, Sivakumar; Johnson, Jeyaraj Antony (Frontiers in Marine Science, 2023)
The Andaman and Nicobar Islands, India, a geographically remote region, harbor a diverse island ecosystem. Limited exploration has hindered our understanding of marine floral biodiversity in this area. To address this gap, we investigated seagrass meadows in the Andaman and Nicobar Islands to understand their spatial distribution, species composition, and habitat characteristics. We assessed 66 seagrass meadows, including 32 newly discovered ones, filling data gaps in the region’s seagrass coldspots. Seagrasses were found across a wide range of depths, with the majority occurring in shallow subtidal waters (< 8 m). Large-sized species such as Thalassia hemprichii, Enhalus acoroides, Cymodocea rotundata, Cymodocea serrulata, and Syringodium isoetifolium dominated the littoral and shallow subtidal zones, while smaller species such as Halophila spp. and Halodule spp. exhibited broader depth distributions. H. beccarii and H. decipiens were strictly intertidal and subtidal species, respectively. Water depth significantly influenced seagrass occurrence (p < 0.0001), cover (β = -0.2759; SE = 0.02471; p < 0.0001), shoot densities (β = -0.3556; SE = 0.1231; p = 0.005), and biomass (β = -0.3526; SE = 0.1159; p = 0.003). Sand availability emerged as the second significant predictor of seagrass distribution, cover, and biomass (p values < 2e-16, < 2e-16, and 0.01, respectively). Habitat heterogeneity decreased with increasing water depth, and seagrass species exhibited strong preferences for specific substrata, resulting in spatial niche partitioning. Our study provides novel insights into the seagrass spatial diversity, habitat characteristics, and seagrass-environment relationship in the Andaman and Nicobar Islands. Further, it highlights the importance of water depth, habitat characteristics, and substratum heterogeneity in seagrass distribution and growth. Lastly, our findings imply that any change to the benthic profile of the meadows will influence the seagrass species distribution and growth. Understanding these factors is crucial for seagrass conservation and management in the region, aiding the development of targeted strategies to protect these valuable marine habitats and associated biodiversity.